مدنی دور نبوی میں عدل و انصاف کے اصول و ضوابط کا تجزیاتی مطالعہ: An Analytical Study of The Principles and Regulations of Justice and Fairness in The Mādanī Era of The Prophet - Muhammad Owais; Dr. Hafiz M. Mudassar Shafique (Al Manhal Research Journal, 2025)
Every society can fall into decay due to the imbalance, oppression, deprivation and class distinctions within it unless its foundation is built on justice and fairness. Social justice, that is, giving every individual his or her legitimate rights, is an indispensable principle for the well-being and survival of nations. In Islamic teachings, justice is not just a principle of law but the soul of human society. Islamic society is not just a collection of acts of worship or jurisprudential rules but a comprehensive social system that guarantees justice and equality. This society, established under the leadership of the Holy Prophet (PBUH) was a "covenant of justice" where neither the powerful enjoyed undue advantage nor the weak faced deprivation. The Mādanī era of the Prophet Muhammad (peace be upon him) was a practical expression of this teaching, in which not only the political and social system of Islam was established, but also justice and fairness were made the basis of state policy. The main objective of this research is to see how the principles of social justice were practically implemented in the Mādanī state and how their effects were structured on social reform. The Prophet (peace be upon him) created a society that was based on justice and brotherhood despite ethnic, religious and economic diversity. This model is an example worthy of imitation for today. In the contemporary world, as social discrimination, inequality and injustice are increasing, the study of the teachings and social structures of the Mādanī era of the Prophet has become very important. This research will not only examine the nature and implementation of social justice of that era but also clarify how these principles can be implemented in today's Muslim societies to reform society.